THE USE OF CONTEXTUAL TEACHING IN TEACHING SPEAKING SKILL IN EFL CLASSROOM - Widiyani Styati, Erlik (Jurnal Pendidikan, 2012)
Learning a foreign language, the learnersÂ needÂ to comprehend the language well. It is needed to undestand and apply in daily life. It also expresses a concept or an idea to communicate with other learners. Besides, the learners still find difficulty in expressing the concept or an idea while learning English as a foriegn language. Otherwise, the learners also still find difficulty in responding and applying the language well. It is meant that they lack to recognized what the studentsâ learning. Overcoming this problem is very important. Furthermore, the paper aims to explain the use of contextual teaching in EFL classroom. It is used in the English skills especially used in speaking. Speaking skill is important skill used in English daily life. Moreover, contextual teaching is appropriate strategy in teaching speaking skill. The strategies are used by the teacher to solve the students problem. The learners will be able to understand and apply the skill in daily life. The paper presents the contextual teaching used in the speaking skill. It can help the learners in applying the foreign language.Â Keywords: speaking, contextual teaching